Organ-on-a-chip technology: a novel approach to investigate cardiovascular diseases. Issue 14 (17th March 2021) - Paloschi, Valentina; Sabater-Lleal, Maria; Middelkamp, Heleen; Vivas, Aisen; Johansson, Sofia; van der Meer, Andries; Tenje, Maria; Maegdefessel, Lars
Abstract: The development of organs-on-chip (OoC) has revolutionized in vitro cell-culture experiments by allowing a better mimicry of human physiology and pathophysiology that has consequently led researchers to gain more meaningful insights into disease mechanisms. Several models of hearts-on-chips and vessels-on-chips have been demonstrated to recapitulate fundamental aspects of the human cardiovascular system in the recent past. These 2D and 3D systems include synchronized beating cardiomyocytes in hearts-on-chips and vessels-on-chips with layer-based structures and the inclusion of physiological and pathological shear stress conditions. The opportunities to discover novel targets and to perform drug testing with chip-based platforms have substantially enhanced, thanks to the utilization of patient-derived cells and precise control of their microenvironment. These organ models will provide an important asset for future approaches to personalized cardiovascular medicine and improved patient care. However, certain technical and biological challenges remain, making the global utilization of OoCs to tackle unanswered questions in cardiovascular science still rather challenging. This review article aims to introduce and summarize published work on hearts- and vessels-on chips but also to provide an outlook and perspective on how these advanced in vitro systems can be used to tailor disease models with patient-specific characteristics.